Can the technologically advanced policy achieve green innovation of small and medium-sized enterprises?—The case of China - Huang, Dawei; Chen, Gang (Frontiers in Environmental Science, 2022)
The purpose of this study is to apply a multidimensional fixed-effects difference-in-differences(DID) model to empirically examine the impact, policy mechanism, and heterogeneity of Technologically Advanced Policy (TAP) on green innovation in small and medium-sized enterprises (SMEs), based on the data of China's A-share listed companies from 2004 to 2021. The results show that TAP significantly improves the green innovation level of listed companies on the small and medium-sized board, and has a more significant role in promoting technologically advanced enterprises (TAEs). The results of the policy effect are still robust after the placebo test, changing the dependent variable, and controlling for the influence of the environmental inspection system, the emissions trading system (ETS), and the carbon emissions trading system (CETS). Furthermore, we find that the policy effect of TAP is better in state-owned SMEs and SMEs in the eastern, central, and western regions. In addition, further research shows that the green innovation effect of TAP is mainly realized through mechanisms such as government subsidy, tax reduction, credit financing, and market competition. Moreover, state-owned SMEs have obvious advantages in the three mechanisms of government subsidy, tax reduction, and market competition, while private SMEs only have significant advantages in credit financing mechanisms. Overall, our findings show that TAP has achieved policy effects in promoting green innovation for SMEs in China, but state-owned SMEs still receive significant policy preference. It is recommended that future policy reforms favor private SMEs.